Structural and Electrical Properties of Nb3I8 Layered Crystal - Kim, Bum Jun; Jeong, Byung Joo; Oh, Seungbae; Chae, Sudong; Choi, Kyung Hwan; Nanda, Sitansu Sekhar; Nasir, Tuqeer; Lee, Sang Hoon; Kim, Kwan Woo; Lim, Hyung Kyu; Chi, Linlin; Choi, Ik Jun; et al. (Physica Status Solidi - Rapid Research Letters, 2019)
Centimeter-size single-crystalline Nb3I8, a new family of two-dimensional materials, is first synthesized by a vapor transport reaction of niobium and iodine. Through the mechanical exfoliation method, the bulk Nb3I8 crystal is cleaved to monolayer and multi-layered flakes. It is confirmed to consist of numerous monolayers of Nb3I8 bonded by weak van der Waals interaction. By utilizing atomic force microscopy (AFM) and scanning Kelvin probe microscopy (SKPM), the information on structure and electrical properties is obtained at the same time. The analysis results show that the surface potential difference and the work function tend to increase as the Nb3I8 becomes thicker due to the interlayer screening effect. The results for the work function variation dependence on thickness are useful for selecting a suitable metal electrode for future Nb3I8-based nano-devices which can have a significant impact on performance.
Keywords: Mechanical exfoliation; Nb3I8; Scanning Kelvin probe microscopy; Structural and electrical properties; Two-dimensional materials; Van Der Waals interactions; Vapor transport; Vapor-transport reaction; Nb3I8; scanning Kelvin probe microscopy; two-dimensional materials; vapor transport